O ensino colaborativo nas práticas pedagógicas: possibilidades para a efetivação de uma escola para todos na educação básica - Alves, Denizia Rosa Ferreira (2022)
The theme of this study is "Collaborative teaching in pedagogical practices: all the possibilities for carrying out basic education for basic education", which has as main objective to investigate the possibilities of action of several students involved in school education through practical practices. The educational product elaborated was a "Collection of Short Films", in the context of the Stricto Sensu Professional Master's Course of the Graduate Program in Teaching in Basic Education of the Center for Teaching and Research Applied to Education (CEPAE) of the Federal University of Goiás ( UFG). The interest in developing an in-depth study on this subject from the experiences in the classroom and the perception that the inclusion of all students in the school comes more than ever. To guide the investigation, this project has the following question as a problem: To include, through collaborative actions, all students in the teaching-learning process, without there being/class/exclusion of subjects?”. To support this work, we chose as the theoretical basis of the research the authors Jacques Rancière (2010), Maria José Esteve de Vasconcellos (2006), Maria Teresa Eglér Mantoan (2015) and Paulo Freire (2021), in addition to the Sparse Legislation and the Federal Constitution. Brazilian (1988). The professional methodological path traced by action research outlines with the participation of their projects, managers, parents, in general and different areas of knowledge, who, voluntarily, added personal and experiences to our project. Finally, we developed a collaborative network with these participants, with a view to systemic thinking. The development of the research with the students of Colégio Estadual Olavo Bilac led us to verify that each subject there can experience an emancipation and autonomy in the construction of knowledge. The production of short films educandos was a demonstration of how far can go when seen as having the ability not only to learn, but to teach, to contribute with all their creative potential.